Against Patriarchy In Khaled Hosseini's A Thousand Splendid Sung (2007) Novel: A Feminist Approach - Agustina, Laili (2012)
The major problem of this study is how against patriarchy is reflected in A Thousand Splendid Suns novel by Khaled Hosseini. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on the feminist analysis. In analyzing A Thousand Splendid Suns, the writer uses qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is A Thousand Splendid Suns novel and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author's biography, the information of Afghanistan country and the other relevant information to analysis of this research. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, from the structural analysis of the novel, it shows that Khaled Hosseini wants to illustrate and convey his idea about how women are subordinated and exploited in patriarchal culture and how to speak against patriarchy. Second, based on Feminist Approach, the conclusion is that there is against patriarchy in the Khaled Hosseini's A Thousand Splendid Suns novel. Hosseini creates that the inner strength of women will be more than the strength of men when they show up. He makes the paradigm that women are not always weak, incapable and depending on men. Women's character can break the type of women's position, right, role and participation that are categorized by patriarchal culture. Therefore, the ability of women to speak against patriarchy is categorized as a feminist attitude.